Green glass - Wan Mazlina, Wan Mehammud; Nurul Hanani, Mohd Redzuan; Noridah, Yangman, Datin; Faizul, Che Pa; Mohamed Faisol, Mohamed Nor (Ministry of Education, Thailand, 2012)
Wan Mazlina and her team won Hong Kong Special Award at 8th International Exhibition for Young Inventors (IEYI 2012), 28th - 30th June 2012 was held at Bangkok International Trade and Exhibition Centre (BITEC), Bangkok, Thailand.